A concise lexicon of late biblical Hebrew : linguistic innovations in the writings of the Second Temple period - Hurvitz, Avi. (Vetus Testamentum, Supplements, 2014)
The Hebrew language may be divided into the Biblical, Mishnaic, Medieval, and Modern ‎periods. Biblical Hebrew has its own distinct linguistic profile, exhibiting a diversity of styles ‎and linguistic traditions extending over some one thousand years as well as tangible diachronic ‎developments that may serve as chronological milestones in tracing the linguistic history of ‎Biblical Hebrew. Unlike standard dictionaries, whose scope and extent are dictated by the contents of the ‎Biblical concordance, this lexicon includes only 80 lexical entries, chosen specifically for a ‎diachronic investigation of Late Biblical Hebrew. Selected primarily to illustrate the fifth-century 'watershed' separating Classical from ‎post-Classical Biblical Hebrew, emphasis is placed on 'linguistic contrasts' illuminated by a rich collection ‎of examples contrasting Classical Biblical Hebrew with Late Biblical Hebrew, Biblical Hebrew with Rabbinic Hebrew, and Hebrew with Aramaic.‎